Well-posedness of a mixed type problem for the multidimensional hyperbolic-parabolic equation - Serik Aimurzaevich Aldashev (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2020)
We consider the modeling multidimensional hyperbolic-parabolic equation in the cylindrical area of Euclidean space and formulate the mixed problem with non-homogeneous boundary conditions for it. We show the unique solvability of the problem for the class of continuously differentiable functions and give a way to construct its explicit classical solution.